Pod-Like Supramicelles with Multicompartment Hydrophobic Cores Prepared by Self-Assembly of Modified Chitosan - Wang, Yiming; Wang, Jie; Wang, Tongshuai; Xu, Yisheng; Shi, Lei; Wu, Yongtao; Li, Li; Guo, Xuhong (Nano-Micro Letters, 2015)
In this paper, pod-like supramicelles with multicompartment hydrophobic cores were prepared by self-assembly of amphiphilic N-phthaloylchitosan-g-poly(N-vinylcaprolactam) (PHCS-g-PNVCL) in aqueous medium. The employed biocompatible amphiphilic polymer was synthesized by grafting the carboxyl terminated poly(N-vinylcaprolactam) (PNVCL-COOH) chains onto N-phthaloylchitosan (PHCS) backbone. 1H NMR and FTIR results confirmed the molecular structure of the copolymers. The morphology of the supramicelles assembled by PHCS-g-PNVCL was revealed by means of TEM and polarized light microscope. In solution, the supramicelles were very stable as monitored by DLS and zeta potential measurements. Temperature and pH presented significant influences on the size and size distribution of the supramicelles. These supramicelles with multicompartment hydrophobic cores should be ideal biomimetic systems with promising applications in drug delivery.